Risk Management in Islamic Banking: A Comparative Study of Islamic vs Conventional Banking Systems - Tantri Octora Dwi Syah Putri; Ami Nullah Marlis tanjung; Zahrina Razali (INTERNATIONAL, Journal of Sharia Business Management, 2024)
This article aims to determine the differences in risk management between Islamic banking and conventional banking and the importance of risk management in the company. The article was created using a qualitative method by obtaining sources from literature studies in the form of books, journals, websites, and other supporting sources related to the article. In risk management, both banks have differences, namely in the risks applied, in conventional banking, namely Credit Risk, Market Risk, Liquidity Risk, Operational Risk, Legal Risk, Strategic Risk, Compliance Risk, Reputation Risk which are different in Islamic banking risk management, there are additional Return Risk and Investment Risk (equity investment risk). In the practice of Islamic banking risk management based on sharia principles by ensuring that all transactions and operations are in accordance with sharia such as the prohibition of usury, gharar, and maysir and using contracts in every transaction. While in conventional banking, the focus is on maintaining the bank's financial health by minimizing losses due to bad debts and interest rate fluctuations.